Analysing University Spoken Interaction : a CL/CA approach - Walsh, Steve (2021)
In this paper, I consider how corpus linguistics (CL) and conversation analysis (CA) can be used together to provide enhanced understandings of spoken interaction in the context of small group teaching in higher education. From an analysis of the data, I show how the two approaches can be combined in an iterative process to account for features of spoken discourse at both micro (word) and macro (text) levels. Beginning with CL and focusing largely on words and combinations of words, CA is then used to highlight pertinent interactional features. The methodology follows an iterative process: from CL to CA, back to CL and so on. This approach to analysis provides powerful insights into the ways in which interactants establish understandings in educational settings and, in particular, highlights the inter-dependency of words, utterances and text in the co-construction of meaning. The aim is to consider how corpus linguistics (CL) and conversation analysis (CA) can be used together to generate fine-grained descriptions of spoken interaction. While CA and CL have both been used on their own to study spoken encounters, each has its limitations. CL, for example, largely ignores context and focuses on large scale analysis, whereas CA offers detailed descriptions but is unable to generalise to larger contexts. Using a combined CL and CA approach (henceforth, CLCA), we argue, cumulatively gives a more ‘up-close’ description of spoken interactions in an educational setting than that offered by using either one on its own. From the analysis